Land-Use Change Analysis of National Southern Cross Road Route Development in Bantul Regency - Kafafa Utia (EDP Sciences, 2021)
The National Southern Cross Road Route well known as Jalan Jalur Lintas Selatan (JJLS) in Indonesia. The segment which crosses Bantul Regency has 16.65 km long. The development of JJLS will have various kinds of impacts on the community around the road infrastructure. This study wants to know how the impact of the development that saw from the spatial dynamics of land-use change. The study area is located in Poncosari, Gadingsari, Srigading, Tirtohargo, and Parangtritis Village. We process the data using the map overlay technique then analyze it with quantitative descriptive. The results of this study are the development of JJLS in Bantul Regency has not significantly affected the land-use changes. It is evident from the location of the land-use change which is far from the road and tends to be disheveled. The Land-use changes that occur do not form a specific pattern such as the pattern of conversion of agricultural land into non-agricultural land. The less significant changes in land use are caused by the condition of the JJLS which is not yet fully connected. Moreover, the status of land ownership around JJLS is Sultan Ground so a special permit is needed if the community wants to use the land.